2012
DOI: 10.1002/j.2333-8504.2012.tb02305.x
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Analysis of Keystroke Log Data From a Timed Writing Task

Abstract: Since its 1947 founding, ETS has conducted and disseminated scientific research to support its products and services, and to advance the measurement and education fields. In keeping with these goals, ETS is committed to making its research freely available to the professional community and to the general public. Published accounts of ETS research, including papers in the ETS Research Report series, undergo a formal peer-review process by ETS staff to ensure that they meet established scientific and professiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
35
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 11 publications
2
35
0
2
Order By: Relevance
“…Several broad trends have been observed relating pause patterns during writing with the quality of the resulting text (Alves, Branco, Castro, & Olive, ; Connelly, Dockrell, Walter, & Critten, ; Hayes, ; Kaufer, Hayes, & Flower, ; Miller, ; van den Bergh & Rijlaarsdam, ; Wengelin, ). Similar results have been obtained in prior published research at Educational Testing Service (ETS), including studies by Almond, Deane, Quinlan, Wagner, and Sydorenko (), Deane and Quinlan (), and Deane, Quinlan, and Kostin (). In particular, for stronger writers, text tends to be produced efficiently in longer bursts; pauses are more likely to happen at natural loci for planning such as clause and sentence boundaries, and more editing and revision behavior can be observed.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…Several broad trends have been observed relating pause patterns during writing with the quality of the resulting text (Alves, Branco, Castro, & Olive, ; Connelly, Dockrell, Walter, & Critten, ; Hayes, ; Kaufer, Hayes, & Flower, ; Miller, ; van den Bergh & Rijlaarsdam, ; Wengelin, ). Similar results have been obtained in prior published research at Educational Testing Service (ETS), including studies by Almond, Deane, Quinlan, Wagner, and Sydorenko (), Deane and Quinlan (), and Deane, Quinlan, and Kostin (). In particular, for stronger writers, text tends to be produced efficiently in longer bursts; pauses are more likely to happen at natural loci for planning such as clause and sentence boundaries, and more editing and revision behavior can be observed.…”
supporting
confidence: 89%
“…For each keystroke timing and process feature, we calculated three summary values: the mean, the standard deviation of durations, and the normalized amount of the total time that each event type occupies in the keystroke timing log. However, preliminary analyses indicated that one version of the summary feature—the standard deviation of pause durations, rather than the average or normalized value—generally showed more consistency in size and magnitude across tasks for the same student, possibly because of the highly skewed nature of the underlying distributions (Almond et al, ; Deane, ). In the analyses presented hereafter, we therefore focused on this class of summary feature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The keystroke logging data were analyzed to identify several key event types previously identified from the writing literature (Almond, Deane, Quinlan, & Wagner, ) using a segmentation program that identified word and sentence boundaries from local cues, such as white space and punctuation marks. The analysis identified bursts (sequences of keystrokes without long pauses), cut/paste/jump events, backspacing events, and several types of pauses (between characters within a word, between words, and between sentences, among others).…”
Section: Methodsmentioning
confidence: 99%
“…Where possible, we selected features where there was a significant correlation greater than .2 between the feature value obtained for this feature in the word listing item and the corresponding feature value for the knowledge elicitation item in at least one of the four forms. Many of the features identified in this way were in the initial set of features described by Almond, Deane, Quinlan, and Wagner (). The features could be defined meaningfully without missing data, even for behaviors like editing, in which the data were very sparse. We thus favored features for which we could provide meaningful default values for feature calculation. If possible, the feature was related to one of the factors we identified in previous work (Deane, ; Deane & Zhang, ; Zhang & Deane, ), in particular, planning and deliberation, fluency (or keyboarding effort), and effort put into local editing or revision.…”
Section: Methodsmentioning
confidence: 99%